Cognitive Enhancement Induced by Anodal tDCS Drives Circuit-Specific Cortical Plasticity. (10th February 2017) - Pisoni, Alberto; Mattavelli, Giulia; Papagno, Costanza; Rosanova, Mario; Casali, Adenauer G; Romero Lauro, Leonor J
Abstract: Increasing evidence shows that anodal transcranial direct current stimulation (tDCS) enhances cognitive performance in healthy and clinical population. Such facilitation is supposed to be linked to plastic changes at relevant cortical sites. However, direct electrophysiological evidence for this causal relationship is still missing. Here, we show that cognitive enhancement occurring in healthy human subjects during anodal tDCS is affected by ongoing brain activity, increasing cortical excitability of task-related brain networks only, as directly measured by Transcranial Magnetic Stimulation combined with electroencephalography (TMS-EEG). Specifically, TMS-EEG recordings were performed before and after anodal tDCS coupled with a verbal fluency task. To control for effects of tDCS protocol and TMS target location, 3 conditions were assessed: anodal/sham tDCS with TMS over left premotor cortex, anodal tDCS with TMS over left posterior parietal cortex. Modulation of cortical excitability occurred only at left Brodmann's areas 6, 44, and 45, a key network for language production, after anodal tDCS and TMS over the premotor cortex, and was positively correlated to the degree of cognitive enhancement. Our results suggest that anodal tDCS specifically affects task-related functional networks active while delivering stimulation, and this boost of specific cortical circuits is correlated to the observed cognitive enhancement.